IoT-based Smart Storage System Using Peltier Technology - Vijayashaarathi.S; Saranya. K; Viswesvaran. K. E; Sakthi Sruthi. K. S (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Cold storage is an essential component in the food industry to maintain the quality and safety of perishable goods. However, traditional cold storage systems have certain drawbacks, including high energy consumption, environmental concerns, and maintenance issues. To overcome these challenges, this paper proposes a Smart Cold Storage System with Peltier technology and IoT. The proposed system utilizes Peltier modules, DHT11 sensors, and Load cell sensors with HX711 to monitor the temperature, humidity, and weight of the stored goods. A custom-built IoT app is also developed to remotely monitor and control the storage conditions of cold storage. The proposed system provides a cost-effective and sustainable solution for cold storage needs while also addressing the challenges of traditional cold storage systems.